Impact of different exercise modalities on neuroendocrine well-being markers among university students: a study of renalase and catecholamine responses - Çınar, Vedat; Bağ, Mehmet Fırat; Aslan, Mehdi; Çınar, Fidan; Gennaro, Alessandro; Akbulut, Taner; Migliaccio, Gian Mario (Frontiers in Physiology, 2025)
Catecholamines (epinephrine, norepinephrine, dopamine) and renalase are among the key biomolecules that regulate stress responses during exercise and support physiological adaptation. However, the effects of different exercise types on these biomolecules remain unclear. This study aims to compare the effects of aerobic, anaerobic, and strength exercises on epinephrine, norepinephrine, dopamine, and renalase levels.Materials and Methods: This study was conducted using a pre-test post-test controlled experimental research design. A total of 80 healthy male participants aged 18–22 years were included and randomly assigned into four groups: control (C), aerobic exercise (A), anaerobic exercise (An), and strength training (Sa). The exercise groups followed specific training protocols for 8 weeks, 3 days per week, at the same time of the day under standardized environmental conditions. Venous blood samples were taken before and after the exercise program, and epinephrine, norepinephrine, dopamine, and renalase levels were analyzed using the ELISA method. Results: Significant increases in epinephrine, dopamine, and renalase levels were observed depending on the exercise type (p < 0.01), while norepinephrine levels showed a significant decrease only in the aerobic exercise group (p < 0.05). Epinephrine levels increased in the aerobic (36.96%), anaerobic (35.42%), and strength training (27.45%) groups, while norepinephrine levels decreased only in the aerobic exercise group (6.38%). Dopamine levels increased in all exercise groups, with the highest change observed in the anaerobic exercise group (38.34%). Renalase levels increased in all exercise groups (p < 0.01), with the highest increase recorded in the anaerobic exercise group (29.42%).Conclusion: This study demonstrated that different exercise modalities induce specific neuroendocrine responses. All exercise types led to significant increases in epinephrine, dopamine, and renalase levels, with the most pronounced effects observed in the anaerobic exercise group. Strength training also produced similarly robust responses. Norepinephrine levels showed a significant decrease only in the aerobic exercise group, while non-significant reductions were observed in the other exercise groups. These findings indicate that exercise type distinctly modulates hormonal and enzymatic pathways involved in physiological adaptation.